Evaluating Gross Anatomy of Cervix in Zel Sheep - Behrokh Marzban Abbasabadi; Hossein Kochakzadeh; Alireza Kaveh Aski (Negah Institute for Scientific Communication, 2019)
Introduction: Many previous studies have proved that the anatomical features of cervix can affect the success of artificial insemination. These characteristics differ in sheep breeds. This study aimed to describe the anatomical features of cervix in Zell ewes; the only tailed sheep in Iran. Methods: Eighty nonpregnant and clinically healthy reproductive tracts of adult Zel sheep were collected from a slaughter house. Based on the estrous cycle, the specimens were divided into follicular or luteal phase. Then, the morphology of the vaginal protrusion of cervix was classified as slit, papilla, duckbill, flap or rose. The cervices were sectioned longitudinally, and the length, number of cervical rings and the arrangement of the rings were recorded.  Results: The results showed the duckbill type was more common in vaginal protrusion of cervix. The mean length of cervix was 61.25±2.88 mm during follicular phase and 63.27±2.56 mm in luteal phase. The mean number of cervical ridges was 7.4 and cervices with a series of complete aligned cervical rings lying across the opened lumen were predominant. However, incomplete ridges and closed cervical canal were observed in some specimens. In 42.85% of cervices, the distance between first and second ridge were significantly more than the distance between other ridges. Conclusion: The results showed that the anatomical characteristics of cervix in Zel sheep may lower the fertility chance through the Transcervical Artificial Insemination. However, the long distance between first and second cervical fold that has been observed in many cases may be suitable for intracervical insemination.